Maintenance of multi-domain neurocognitive functions in patients with newly-diagnosed primary CNS lymphoma after primary cranial radiotherapy combined with methotrexate-based chemotherapy: A preliminary case-series study. Issue 3 (4th May 2022) - Lin, Shinn-Yn; Chuang, Chi-Cheng; Tsan, Din-Li; Hung, Yu-Shin; Fu, Chen-Ju; Shen, Yi-Liang; Chiang, Yin-Yin; Huang, Yin-Cheng; Lu, Yu-Jen; Yang, Chi-Cheng
Abstract: Conventional treatment for treating primary central nervous system lymphoma (PCNSL) has consisted of either whole-brain radiotherapy (WBRT) or methotrexate (MTX)-based combined modality therapy. However, delayed cognitive sequelae have emerged as a significant debilitating complication in PCNSL patients. A prospective observational case-series study with prospective assessments of neurocognitive functions (NCFs), neuroimaging, and activities of daily living in newly-diagnosed PCNSL patients was undertaken. A battery of neuropsychological measures, used to evaluate NCFs, is composed of ten standardized NCF tests, representing four domains sensitive to disease and treatment effects (executive function, attention, verbal memory, psychomotor speed), and activities of daily living. A total of 15 patients with newly-diagnosed PCNSL were consecutively enrolled in this study. Comparing the NCF scores between the baseline (before WBRT) and post-treatment (after combined chemoradiation therapy) intervals (Mean = 122.33 days, SD = 34.49, range = 77–196), neurobehavioral outcomes consistently remained improving or stable in almost each domain of NCF. Specifically, the scores on Paced Auditory Serial Addition Test—Revised (PASAT-R) were significantly improved between the baseline and post-chemoradiation assessment. Under the multidisciplinary treatment guidelines for treating patients with newly-diagnosed PCNSL, multi-domain NCF become stabilized and even improved after the course of conformal WBRT combined with or without MTX-based chemotherapy.